Smart traffic signal control for multi-junctions - Wang, Yu (2016)
Along with economic growth and more affluence of population, traffic congestion has become a severe and growing problem in modern cities since more and more vehicles enter urban public road network with limited capacities. Traffic signal management is recognized as one of the most efficient ways to improve urban network congestion. Various signal control strategies have been proposed and applied all over the world in the past decades, which greatly improve traffic conditions. Whereas most of these strategies may not be capable for saturated conditions. Once road is congested, the throughput capacity decreases and in turn causes further deterioration of network congestion. Therefore, intelligent urban traffic control is an urgent need for regulating urban traffic systems to satisfy large fluctuating traffic demands. Furthermore, new motivations for traffic signal control research are the coming of new technologies such as fast communication systems, accurate sensing and network systems etc. \\